2012
DOI: 10.1371/journal.pgen.1002550
|View full text |Cite
|
Sign up to set email alerts
|

APOBEC3G-Induced Hypermutation of Human Immunodeficiency Virus Type-1 Is Typically a Discrete “All or Nothing” Phenomenon

Abstract: The rapid evolution of Human Immunodeficiency Virus (HIV-1) allows studies of ongoing host–pathogen interactions. One key selective host factor is APOBEC3G (hA3G) that can cause extensive and inactivating Guanosine-to-Adenosine (G-to-A) mutation on HIV plus-strand DNA (termed hypermutation). HIV can inhibit this innate anti-viral defense through binding of the viral protein Vif to hA3G, but binding efficiency varies and hypermutation frequencies fluctuate in patients. A pivotal question is whether hA3G-induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
66
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(74 citation statements)
references
References 77 publications
(116 reference statements)
5
66
1
2
Order By: Relevance
“…Specifically, we observed that G-to-A mutations occurred more frequently in APOBEC3G-disfavored contexts than in APOBEC3G-favored contexts, strongly suggesting that APOBEC3G activity does not contribute to beneficial HIV-1 diversification in vivo. This result is consistent with our previous in vitro and in silico analyses of APOBEC3G, which indicated that the activity of even a single APOBEC3G unit is highly likely to be lethal for HIV-1 (21).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Specifically, we observed that G-to-A mutations occurred more frequently in APOBEC3G-disfavored contexts than in APOBEC3G-favored contexts, strongly suggesting that APOBEC3G activity does not contribute to beneficial HIV-1 diversification in vivo. This result is consistent with our previous in vitro and in silico analyses of APOBEC3G, which indicated that the activity of even a single APOBEC3G unit is highly likely to be lethal for HIV-1 (21).…”
Section: Discussionsupporting
confidence: 93%
“…induced mutagenesis (12,21), the limitation that we are not able to compare the mutational context in the same gene is unlikely to affect the results.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…With a lower gene inactivation potential and a high rate of NS substitution generation, our results support that A3F is much more effective than A3G at promoting viral sequence evolution. This is also consistent with previous findings that employed other analysis methods and systems (Ara et al, 2014;Armitage et al, 2012Armitage et al, , 2014Kim et al, 2014;Sato et al, 2014;Wood et al, 2009).…”
Section: A3fsupporting
confidence: 93%
“…This thereby provided us with the ability to directly compare how DNA target specificity impacts gene inactivation and retroviral sequence evolution. This is an issue of particular importance as A3F, more than A3G, has been shown to promote HIV-1 diversification and evolution in vivo (Ara et al, 2014;Armitage et al, 2012Armitage et al, , 2014Kim et al, 2014;Sato et al, 2014;Wood et al, 2009). However, the extent to which this diversification correlates with alterations in gene function had not been assessed until now.…”
Section: A3fmentioning
confidence: 99%